In Vitro and In Vivo Studies of Anti-Lung Cancer Activity of Artemesia judaica L. Crude Extract Combined with LC-MS/MS Metabolic Profiling, Docking Simulation and HPLC-DAD Quantification - Marwa S. Goda; Mohamed S. Nafie; Basma M. Awad; Maged S. Abdel-Kader; Amany K. Ibrahim; Jihan M. Badr; Enas E. Eltamany (MDPI AG, 2021)
Artemisia judaica L. (Family: Asteraceae) exhibited antioxidant, anti-inflammatory, and antiapoptotic effects. The in vitro cytotoxic activity of A. judaica ethanolic extract was screened against a panel of cancer cell lines. The results revealed its cytotoxic activity against a lung cancer (A549) cell line with a promising IC50 of 14.2 μg/mL compared to doxorubicin as a standard. This was confirmed through the downregulation of antiapoptotic genes, the upregulation of proapoptotic genes, and the cell cycle arrest at the G2/M phase. Further in vivo study showed that a solid tumor mass was significantly reduced, with a tumor inhibition ratio of 54% relative to doxorubicin therapy in a Xenograft model. From a chemical point of view, various classes of natural products have been identified by liquid chromatography combined with tandem mass spectrometry (LC-MS/MS). The docking study of the detected metabolites approved their cytotoxic activity through their virtual binding affinity towards the cyclin-dependent kinase 2 (CDK-2) and epidermal growth factor receptor (EGFR) active sites. Finally, A. judaica is a fruitful source of polyphenols that are well-known for their antioxidant and cytotoxic activities. As such, the previously reported polyphenols with anti-lung cancer activity were quantified by high-performance liquid chromatography coupled with a diode array detector (HPLC-DAD). Rutin, quercetin, kaempferol, and apigenin were detected at concentrations of 6 mg/gm, 0.4 mg/gm, 0.36 mg/gm, and 3.9 mg/gm of plant dry extract, respectively. It is worth noting that kaempferol and rutin are reported for the first time. Herein, A. judaica L. may serve as an adjuvant therapy or a promising source of leading structures in drug discovery for lung cancer treatment.